2002
DOI: 10.1007/s00266-002-2019-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving Scar Quality: A Prospective Clinical Study

Abstract: Following traumatic or surgical injury to the skin, wounds do not heal by tissue regeneration but rather by scar formation. Though healing is definitely a welcomed event, the resultant scar, very often, is not aesthetically pleasing, and not infrequently, may be pathologic causing serious deformities and contractures. Management of problematic scars continues to be a frustrating endeavor with less than optimal results. Prophylactic methods of wound management to minimize serious scarring are being developed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…The abdominal scar and intra-abdominal adhesions are both results of wound healing, which differs between individuals (6,7). In both processes similar factors are involved, including cellular, immunologic, and hormonal components (11,12).…”
Section: Cesarean Delivery Is a Risk Factor For Adhesion Formation (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…The abdominal scar and intra-abdominal adhesions are both results of wound healing, which differs between individuals (6,7). In both processes similar factors are involved, including cellular, immunologic, and hormonal components (11,12).…”
Section: Cesarean Delivery Is a Risk Factor For Adhesion Formation (3)mentioning
confidence: 99%
“…Adhesion-related complications after cesarean delivery include bowel obstruction, chronic pelvic pain, infertility, and difficult and sometimes complicated repeat surgery (3)(4)(5). Because the abdominal scar of a previous laparotomy and intra-abdominal adhesions are both tissue healing processes (6,7), we aimed in this study to investigate whether specific abdominal scar characteristics found preoperatively could predict the presence and severity of intraabdominal adhesions formed after a previous cesarean delivery.…”
mentioning
confidence: 99%
“…Unfortunately, there are limited biocompatible and biodegradable materials available. Hydrogels have been used as an alternate artificial skin, because good hydration is the most important external factor responsible for optimal wound healing [11][12][13][14], as water is necessary for transport of nutrients to the growing cells. Hydrogels, however, are commonly not physically strong enough to mimic the tough, thin dermis [9].…”
Section: Introductionmentioning
confidence: 99%
“…compared MEBO, an antibiotic ointment, and no topical therapy in patients with traumatic and surgical facial wounds. MEBO was found to produce significantly better results at follow‐up after 1, 3, and 6 months . Other prospective studies of partial‐thickness skin graft donor sites have compared MEBO with conventional wound care and with Tegaderm ® (3M Health Care, St. Paul, MN, USA).…”
Section: Scar Prevention and Remodelingmentioning
confidence: 99%